Electrospinning of calcium phosphate-poly(D,L-lactic acid) nanofibers for sustained release of water-soluble drug and fast mineralization - Fu QW (Dove Medical Press, 2016)
Qi-Wei Fu,1,* Yun-Peng Zi,1,* Wei Xu,1 Rong Zhou,1 Zhu-Yun Cai,1 Wei-Jie Zheng,1 Feng Chen,2 Qi-Rong Qian1 1Department of Orthopedics, Changzheng Hospital, Second Military Medical University, 2State Key Laboratory of High Performance Ceramics and Superfine Microstructure, Shanghai Institute of Ceramics, Chinese Academy of Sciences, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Calcium phosphate-based biomaterials have been well studied in biomedical fields due to their outstanding chemical and biological properties which are similar to the inorganic constituents in bone tissue. In this study, amorphous calcium phosphate (ACP) nanoparticles were prepared by a precipitation method, and used for preparation of ACP-poly(D,L-lactic acid) (ACP-PLA) nanofibers and water-soluble drug-containing ACP-PLA nanofibers by electrospinning. Promoting the encapsulation efficiency of water-soluble drugs in electrospun hydrophobic polymer nanofibers is a common problem due to the incompatibility between the water-soluble drug molecules and hydrophobic polymers solution. Herein, we used a native biomolecule of lecithin as a biocompatible surfactant to overcome this problem, and successfully prepared water-soluble drug-containing ACP-PLA nanofibers. The lecithin and ACP nanoparticles played important roles in stabilizing water-soluble drug in the electrospinning composite solution. The electrospun drug-containing ACP-PLA nanofibers exhibited fast mineralization in simulated body fluid. The ACP nanoparticles played the key role of seeds in the process of mineralization. Furthermore, the drug-containing ACP-PLA nanofibers exhibited sustained drug release which simultaneously occurred with the in situ mineralization in simulated body fluid. The osteoblast-like (MG63) cells with spreading filopodia were well observed on the as-prepared nanofibrous mats after culturing for 24 hours, indicating a high cytocompatibility. Due to the high biocompatibility, sustained drug release, and fast mineralization, the as-prepared composite nanofibers may have potential applications in water-soluble drug loading and release for tissue engineering. Keywords: calcium phosphate, water-soluble drug, nanofibers, drug release, electrospinning